Cultural and other constraints in help seeking with abusive relationships : the narratives of Xhosa-speaking women - Mtini, Nolitha Y (Department of Psychology, 2015)
Little is documented about Xhosa-speaking women's experiences and the social and cultural barriers they are faced with when seeking help for the abuse in their marriages. This study explores the experiences of Xhosa married women who are in abusive relationships and have sought help in a counselling organisation. It traces their path of seeking help before they reached the women's counselling centre. The study was conducted by holding in-depth interviews with eight women who live in a township and its surrounding informal settlements in Cape Town. Their narratives are presented in case studies and the discussion of significant themes is presented in a separate chapter. The study suggests that a number of factors influenced their decision to seek help. The women wanted the abuse to stop rather than to leave their marriages.